2022
DOI: 10.30892/gtg.41220-854
|View full text |Cite
|
Sign up to set email alerts
|

Regional Aspects of Creation Complex Routes Ecological Tourism on the Territory of North Kazakhstan Region

Abstract: To consider the possibility of developing ecological tourism in the districts of the North Kazakhstan region of the Republic of Kazakhstan, based on the conducted sociological research and the available natural and recreational potential. The analysis of the conducted sociological survey is given, using methods of statistical and mathematical processing. Visualization of the presented materials was carried out by means of mapping. The study and analysis of the data obtained allowed us to reveal the natural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The capabilities of these technologies make it possible to process and tidimensional data about the geological environment of the studied territory (Leonova, Strokova, evidence of the growth of gullies, elementary geoinformation systems that are in the public used, namely the modern functions of the Google Earth satellite image retrospective and the of their morphometric analysis. In combination with geoinformation systems, mathematical ethods are used to build predictive models of ravine growth (Dmitriyev et al, 2022). erials and research methods possibilities of geoinformation systems are clearly illustrated by traditional statistical data g the process of ravine formation in dynamics for monitoring and forecasting.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capabilities of these technologies make it possible to process and tidimensional data about the geological environment of the studied territory (Leonova, Strokova, evidence of the growth of gullies, elementary geoinformation systems that are in the public used, namely the modern functions of the Google Earth satellite image retrospective and the of their morphometric analysis. In combination with geoinformation systems, mathematical ethods are used to build predictive models of ravine growth (Dmitriyev et al, 2022). erials and research methods possibilities of geoinformation systems are clearly illustrated by traditional statistical data g the process of ravine formation in dynamics for monitoring and forecasting.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…2024 As evidence of the growth of gullies, elementary geoinformation systems that are in the public domain are used, namely the modern functions of the Google Earth satellite image retrospective and the possibilities of their morphometric analysis. In combination with geoinformation systems, mathematical estimation methods are used to build predictive models of ravine growth (Dmitriyev et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This would reveal the dynamics of both acreage and fertilization areas within the boundaries of the administrative districts of the territory of the studied region. These aspects, combined with the natural resource potential and the presence of recreational, cultural, ethnic, and historical sites, in our opinion, contribute to the development of ecological and agricultural tourism [73][74][75].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire surveys (e.g. in Poland) also spoke in favor of agritourism, which stated directly that in the era of a pandemic, agritourism farms would be a frequent choice (Wojcieszak-Zbierska et al, 2020) which will fit in with the trend for ecological and sustainable tourism (Dmitriyev et al, 2022). A study by Roman and Grudzień (2021) positively confirmed that owning agritourism during the COVID-19 pandemic was profitable.…”
Section: Introductionmentioning
confidence: 99%